Resolving the role of carbonaceous material in gold precipitation in metasediment-hosted orogenic gold deposits - Hu, Siyu; Evans, Katy; Craw, D.; Rempel, Kirsten; Grice, Kliti (Geological Society of America, 2017)
Carbonaceous material (CM) is commonly associated with gold and sulfides in metasediment-hosted orogenic gold deposits. The role of CM in Au deposition is controversial; CM has been proposed to contribute to gold deposition by reducing Au bisulfide complexes, or by facilitating sulfidation, which destabilizes Au in bisulfide complexes with resultant Au deposition. Integration of petrographic observations, thermodynamic models, and geochemical data from metasediment-hosted orogenic gold deposits in New Zealand, Australia, Canada, and West Africa reveals genetic links between sulfides, CM, and mineralization. The results are consistent with the coexistence of CM and pyrite as a consequence of their codeposition from ore fluids, with a minor proportion of CM originally in situ in the host rocks. Au is deposited when pyrite and CM deposition decreases H2S concentration in ore fluids, destabilizing Au(HS)2-complexes. Most CM in gold deposits is deposited from CO2 and CH4 in ore fluids. These findings are applicable to similar deposits worldwide.